SUSTAINABLE DEVELOPMENT OF RESOURCE POTENTIAL IN THE FOOD COMPLEX - Kоreniuk P.I. (The actual problems of regional economy development, 2019)
At present in the country, there is a certain decrease in the consumption of staple foods and calories of the daily diet. In these conditions, the problem of reproduction of natural resources in the food complex from the point of view of sustainable development and efficient use of the agrarian resource potential of the environment is urgent. Assessment of the dynamics of the development of the grain subcomplex of the food complex for rationalization of the structure of grain production and efficient use of the agricultural resource potential of the environment is possible through the evaluation of macroeconomic indicators. Dynamics of quantitative ratios between the gross domestic product of the state and the production of the agrarian sector over a certain period shows an increase in the volume of the gross product per person. The share of agricultural production in the gross product is decreasing steadily, which shows a change in priority types of production. Trends in the development of the natural resource potential of the country's food complex show a decline in agricultural land. In recent years, only the acreage of sunflower, which is a priority export crop, has increased. Strategic direction of crisis resolution may be restructuring of grain subcomplex of processing industries of food complex based on effective utilization of agrarian resource potential of environment. Ukraine has a strong agrarian natural- resource potential due to its favorable economic and geographical position, and there are powerful markets for food and raw materials (EU countries, Russia, China).The depletion of the consumer basket of the able-bodied population in the country against the backdrop of a decrease in the share of agricultural production in the gross product demonstrates a change in priority types of production. At the same time, the reduction of agricultural land area occurs with a constant increase of sunflower acreage, which provokes an imbalance in the activities of the domestic food and processing industry. However, consequently, further reduction of consumption and caloric content of the daily diet, reorientation of food and processing industries to imported raw materials, further decline of domestic agriculture.